Isu Politik dan Identitas Sosial: Respons Emosional Masyarakat terhadap Tuduhan Kepalsuan Ijazah Presiden - Jingga Situngkir, Aisyah Mawar; Kurniawan, Rizal (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine public emotional responses to the allegations of President Joko Widodo's forged academic diploma and to explore the role of social-political identity in shaping these perceptions. A descriptive qualitative approach was employed, involving 251 respondents aged 18 years and above who were eligible to vote. Data were collected through an online open-ended questionnaire distributed via Google Forms and analyzed using coding techniques and thematic analysis. The findings indicate that public responses to the issue are influenced by social-political identity, trust in government institutions, media exposure, and emotional attachment to political figures. Respondents who believed the allegations generally expressed distrust toward the government, suspicion regarding the authenticity of official documents, and were influenced by media coverage or political figures. In contrast, respondents who rejected the allegations based their views on factual evidence, logical reasoning, trust in governmental institutions, and official clarifications. From an emotional perspective, participants exhibited a range of responses, including anger, disappointment, anxiety, confusion, as well as neutral and apathetic attitudes. These findings suggest that public perceptions of political issues are shaped not only by factual information but also by group identity and emotional dynamics within a politically polarized society. This study contributes to the field of political psychology by highlighting the importance of understanding the interaction between social identity, emotions, and political attitude formation in responding to controversial political issues.